2020
DOI: 10.1002/jcla.23397
|View full text |Cite
|
Sign up to set email alerts
|

The association between circulating MicroRNA‐150 level and cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a rare tumor comprising approximately 3% of gastrointestinal tumors with an overall incidence of less than 2/100 000. It is the second most common primary hepatic malignancy following hepatocellular carcinoma (HCC). 1,2 CCA incidence has been increasing globally during the last decades, where its incidence increases with age. 3 According to the anatomic location, CCA is classified into intrahepatic (IH-CCA) and extrahepatic (EH-CCA) where the later accounts for 80%-90% of all cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…While reduced levels of miR-150 were observed in individuals with CCA, another study reported an upregulation of miR-150 in patients suffering iCCA. Remarkably, the combination of reduced miR-150 and increased CA19-9 seemed to improve the accuracy of CCA diagnosis [ 58 ]. Expression of miRNAs was further investigated in bile samples and correlated with CCA occurrence; however, their prognostic value remains inconclusive [ 57 ].…”
Section: Prognostic Serum Biomarkersmentioning
confidence: 99%
“…While reduced levels of miR-150 were observed in individuals with CCA, another study reported an upregulation of miR-150 in patients suffering iCCA. Remarkably, the combination of reduced miR-150 and increased CA19-9 seemed to improve the accuracy of CCA diagnosis [ 58 ]. Expression of miRNAs was further investigated in bile samples and correlated with CCA occurrence; however, their prognostic value remains inconclusive [ 57 ].…”
Section: Prognostic Serum Biomarkersmentioning
confidence: 99%
“…Nevertheless, similarly to ctDNA/cfDNA detection in plasma, the identification of miRNA should be interpreted with caution since this biomarker can also be identified in the serum of patients affected by HCC or other liver diseases[ 175 ]. Several other circulating miRNAs have shown potential as biomarkers with the ability to discriminate between CCA and other liver diseases[ 176 - 179 ]. Loosen et al [ 177 ] analyzed the concentrations of a 4 miRNAs panel (miR-122, miR-192, miR-29b and miR-155) in serum samples from 94 patients with CCA undergoing surgical resection and 40 healthy controls.…”
Section: Lb In Ccamentioning
confidence: 99%
“…They are a good source for molecular markers in the blood. They are of three kinds: microvesicles, exosomes, and apoptotic bodies ( 97 , 98 ).…”
Section: Precision Medicine In Biliary Tract Cancer: Current State and Future Directionsmentioning
confidence: 99%